SARS-CoV-2: tracing the origin, tracking the evolution - Konstantinos Voskarides (BMC, 2022)
Abstract The origin of SARS-CoV-2 is uncertain. Findings support a "bat origin" but results are not highly convincing. Studies found evidence that SARS-CoV-2 was around for many years before the pandemic outbreak. Evidence has been published that the progenitor of SARS-CoV-2 already had the capability to bind strongly to the human ACE2 receptor. This may be an indication that many other animal viruses are capable to jump to humans, having already affinity for a human receptor. This is quite worrying since current ecosystems' collapse brings people to high proximity with animals, increasing probabilities for random viral transitions. On the other hand, future adaptation of SARS-CoV-2 is of great concern. Virus-host interactions are complicated and unfortunately, we still do not have accurate tools for predicting viruses' future evolution. Viral adaptation is a multifactorial process and probably SARS-CoV-2 will not become soon, as we wish, a harmless infection. However, humanity is currently under the largest vaccination program and it's of great interest to see if vaccinations will change the evolutionary game against the virus.